Importance of histopathological evaluation of appendectomy specimens - Mohamed Abd Al-Fatah (Wolters Kluwer Medknow Publications, 2017)
Background Appendicitis is by far the commonest major emergency general surgical operation. Pathological evaluation of the appendix after appendectomy is routine and can occasionally identify unexpected findings. The objective of this study was to analyze the clinical benefit of histopathological analysis of appendectomy specimens from patients with an initial diagnosis of acute appendicitis. Patients and methods The clinicopathological data of 460 patients who underwent appendectomies for presumed acute appendicitis were reviewed prospectively. Results There were 265 men and 195 women [sex ratio (male/female): 1.4] aged between 16 and 62 years (mean: 27.6 years). All patients underwent open appendectomy. Histological examination of the surgical specimen showed normal appendix in 28/460 (6%) cases, gross inflammation in 365 (79.3%) cases, gangrenous appendix in 32 (7%) cases, perforation and localized peritonitis in 30 (6.6%) cases, and generalized peritonitis in five (1.1%) cases. Incidental unexpected pathological diagnoses were noted in 39 (8.5%) appendectomy specimens. They included Enterobius vermicularis (n=19), mucinous neoplasms (n=3), neuroendocrine tumors (n=1), granulomatous inflammation (n=12), tuberculosis (n=1), bilharziasis (n=1), and endometriosis (n=2). Other associated pathological findings were ruptured ovarian cyst (n=9), perforated duodenal ulcer (n=3), Meckel's diverticulum (n=1), disturbed ectopic pregnancy (n=3), and cecal adenocarcinoma (n=2). Conclusion The diagnosis of acute appendicitis has been improved, with a significant reduction in negative appendectomy rates. Routine pathological examination of appendectomy specimens is of value for identifying unsuspected pathologies requiring further postoperative management. Gross examination alone does not appear to be a good indicator of an unexpected finding on microscopic examination. It is highly recommended that in order to avoid misdiagnoses, all appendix specimens should be examined histopathologically.